2022
DOI: 10.1186/s12889-022-13798-2
|View full text |Cite
|
Sign up to set email alerts
|

Children’s rates of COVID-19 vaccination as reported by parents, vaccine hesitancy, and determinants of COVID-19 vaccine uptake among children: a multi-country study from the Eastern Mediterranean Region

Abstract: Background Huge efforts are being made to control the spread and impacts of the coronavirus pandemic using vaccines. However, willingness to be vaccinated depends on factors beyond the availability of vaccines. The aim of this study was three-folded: to assess children’s rates of COVID-19 Vaccination as reported by parents, to explore parents’ attitudes towards children’s COVID-19 vaccination, and to examine the factors associated with parents’ hesitancy towards children’s vaccination in severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 38 publications
7
29
0
1
Order By: Relevance
“…Our reported rate of COVID-19 vaccine uptake in children at 48.5% is in concordance with a recently published regional study across eight Eastern Mediterranean countries, revealing an interestingly similar rate at 48.9% in the UAE [22]. This similarity in results provides a valuable insight into the progression, or lack thereof, of the vaccination campaign in children, given that the latter study was carried out from November to December of 2021, a few months before the timeframe of our present study.…”
Section: Discussionsupporting
confidence: 93%
“…Our reported rate of COVID-19 vaccine uptake in children at 48.5% is in concordance with a recently published regional study across eight Eastern Mediterranean countries, revealing an interestingly similar rate at 48.9% in the UAE [22]. This similarity in results provides a valuable insight into the progression, or lack thereof, of the vaccination campaign in children, given that the latter study was carried out from November to December of 2021, a few months before the timeframe of our present study.…”
Section: Discussionsupporting
confidence: 93%
“…Quite a large percentage of the local population were hesitant to take the vaccine. Alternatively, Syrian refugees show high willingness to vaccinate their children, with only 13.9% unwilling to do so, which is very low compared with other studies reporting high unwillingness of parents from Arab countries to vaccinate their children [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 72%
“…While only Pfizer has been implemented for those aged 5–11 years, in Italy, the United States, Israel, United Kingdom, Germany, Ireland, Poland, France, Spain and Denmark. [ 210 – 213 , 218 , 223 225 ]. Several studies have shown that vaccines were safe and effective in reducing virus transmission and protecting them against re-infection with SARS-CoV-2 [ 205 , 226 228 ].…”
Section: Sars-cov-2 Vaccines In Childrenmentioning
confidence: 99%